PERMAINAN WHAT’S IN HERE? SEBAGAI ALTERNATIF METODE PEMBELAJARAN UNTUK MELATIHKAN KETERAMPILAN BERTANYA SISWA SEKOLAH DASAR - Selly Nurina Suraya (Universitas PGRI Madiun, 2014)
Abstract Education is a systematic process to improve human dignity in a holistic manner that allows self potentials (affective, cognitive, and psychomotor) develop optimally. Curriculum 2013 adheres to the basic view that knowledge cannot be moved away from the teacher to the learner. For learners, learning should be shifted from